PENGARUH STRATEGI PEMASARAN TERHADAP KEPUTUSAN KUNJUNGAN WISATAWAN PADA KELING KUMANG AGROWISATA - Nanda, Erli Lingga Eka Puspa; Astikawati, Yunita (Jurnal Pendidikan Ekonomi (JURKAMI), 2024)
Tourism is an important sector in the Indonesian economy, especially agrotourism which combines agriculture with tourism. Keling Kumang Agrotourism is a tourist location which is the tourist destination most frequently visited by the people of Sintang. Therefore, this research the study was undertaken with the objective of. obtaining information on the influence of marketing strategies on tourist visits to Keling Kumang Agrotourism. The type of research carried out in this research is quantitative using a causal associative approach. The type of data used is primary data. The population for this research is tourists who have visited and are currently visiting Keling Kumang agrotourism. The sample was 30 tourists using an unintentional checking strategy. The information gathering the strategy was implemented via the execution of predetermined plans and tactics use of a survey using a Likert scale which was tried to investigate speculation. Information from this research was handled using SPSS 26.00. The results of the research show that marketing strategies can be categorized as good with an average classification value of 77. Visiting Decisions are categorized as fair with an average classification value of 73. There is a significant influence by marketing strategy on Visiting Decisions through an R square value of 60, 8, and significant 0.000 < 0.05. This means that there is 39.2 influenced by other factors.